Receptive Language Disorder in “A Boy Called PO 2016” Movie - Dwiyani, Cut Nadira; Afriana, Afriana (e-Journal of Linguistics, 2022)
This study used psycholinguistics approach to discover the symptoms of receptive language disorder in A boy Called Po movie. This study was conducted using qualitative methods. In the process of collecting data, researchers used observational methods and non-participatory techniques proposed by (Sudaryanto, 2015). Data collection was obtained from watching A Boy Called Po movie. Then, the data were analyzed and classified based on symptoms of receptive language disorder according to the theory of (Carroll, 1985 as cited in (Faida, 2020). The result of this study was that the main character of A Boy Called Po movie had a receptive language disorder. Some of the factors that caused receptive language disorder were the main character was not interested in communicating, the main character only focused on what was on his mind without paying attention to his surroundings, and the main character only thought about himself without looking at the condition of others. There were 15 data of receptive language disorder found in the movie. The 15 data consisted of 8 data on not appearing to listen, 4 data on difficulty following verbal communication, 2 data on difficulty in interpreting words or phrases, and 1 data on difficulty understanding complex sentences.